Dissent, Wit, and Metrical Experimentation: Parra, Shakespeare, and the Baroque; [Disenso, Ingenio y Experimentación Métrica: Parra, Shakespeare y el Barroco] - Cussen-Abud, F (Pontificia Universidad Catolica de Chile, 2025)
This article examines the reception of the “literary baroque” of the 16th and 17th centuries in Latin American poetry from the second half of the 20th century. We do so in light of a heterodox example: the antipoetry of Nicanor Parra. We challenge an understanding of the baroque as a monolingual (Spanish) and exclusively counter-reformist phenomenon, to argue, with Peter Davidson (2007), that the baroque was transnational and multilingual, and exceeded the hermeticism and ornamentation of Spanish Golden Age poetry. We use Parra’s example to show that his poetics incorporates another aspect of the baroque—the dissident styles and metrical experimentation of the English tradition, especially the work by Donne and Shakespeare. To do so, we first analyse the metrical experimentation of the baroque in light of the theoretical textbooks of transnational circulation and the application of these theories to the verse of the Elizabethan “wits.” We then analyse how these practices are incorporated and discussed by Parra during the creation of a work that represents a fundamental revision of his antipoetic project: his translation of Shakespeare’s King Lear (1991). Reading Parra from the perspective of the baroque, we suggest, blurs the sharp distinction between colloquialism and neo-baroque in Latin America, reconfiguring our vision of the recent canon of regional and Chilean poetry. © 2025 Pontificia Universidad Catolica de Chile. All rights reserved.